Chromosomal locus rearrangements are a rapid response to formation of the allotetraploid Arabidopsis suecica genome - Pontes, Olga (National Academy of Sciences, 2004)
Allopolyploidy is a significant evolutionary process, resulting in new species with diploid or greater chromosome complements derived from two or more progenitor species. We examined the chromosomal consequences of genomic merger in Arabidopsis suecica, the allotetraploid hybrid of Arabidopsis thaliana and Arabidopsis arenosa. Fluorescence in situ hybridization with centromere, nucleolus organizer region (NOR), and 5S rRNA gene probes reveals the expected numbers of progenitor chromosomes in natural A. suecica, but one pair of A. thaliana NORs and one pair of A. arenosa-derived 5S gene loci are missing. Similarly, in newly formed synthetic A. suecica-like allotetraploids, pairs of A. thaliana NORs are gained de novo, lost, and/or transposed to A. arenosa chromosomes, with genotypic differences apparent between F(3) siblings of the same F(2) parent and between independent lines. Likewise, pairs of A. arenosa 5S genes are lost and novel linkages between 5S loci and NORs arise in synthetic allotetraploids. By contrast, the expected numbers of A. arenosa-derived NORs and A. thaliana-derived 5S loci are found in both natural and synthetic A. suecica. Collectively, these observations suggest that some, but not all, loci are unstable in newly formed A. suecica allotetraploids and can participate in a variety of alternative rearrangements, some of which resemble chromosomal changes found in nature.